2005
DOI: 10.4028/www.scientific.net/amr.6-8.441
|View full text |Cite
|
Sign up to set email alerts
|

Force Measurements for Single Point Incremental Forming: An Experimental Study

Abstract: In this paper an experimental platform capable of measuring forces in process during an incremental forming procedure is described and the results garnered from it are presented. Some of the earliest measurements of forces in incremental forming and the changes induced on the measured load are reported. Using a table type force dynamometer with incremental forming fixture mounted on top, three components of force were measured throughout the forming process. They were found to vary as the parts were made. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 3 publications
4
29
0
Order By: Relevance
“…Duflou et al (2005) found that total tool force in SPIF increases with vertical pitch, tool diameter and wall angle. Bologa et al (2005) measured the influence of sheet thickness, vertical pitch and diameter on vertical and horizontal force and concluded that the sheet thickness had the most significant influence on vertical force.…”
Section: The Mechanics Of Incremental Sheet Formingmentioning
confidence: 96%
“…Duflou et al (2005) found that total tool force in SPIF increases with vertical pitch, tool diameter and wall angle. Bologa et al (2005) measured the influence of sheet thickness, vertical pitch and diameter on vertical and horizontal force and concluded that the sheet thickness had the most significant influence on vertical force.…”
Section: The Mechanics Of Incremental Sheet Formingmentioning
confidence: 96%
“…The forces acting on the tool were measured using a force platform [8,24]. This platform was a Kistler 9265B six-component force dynamometer, used with a multichannel charge amplifier 5017A capable of measuring a vertical force between −15 and 30 kN and two horizontal forces of ±15 kN (see Fig.…”
Section: Experimental Set-upmentioning
confidence: 99%
“…It was concluded [54], that the most segnificant value of the force is for Fz, valid for both to SPIF and TPIF. Duflou et al [55] performed a series of experiments on a reference conical part manufactured by SPIF from five diferent materials. It is measured the forces for differents part configuration and it was concluded with the infuence of sheet thickness, draw angle, tool diameter and step depth ∆z on total forces: -when the sheet thickness is greater, then bigger forces are needed to form the parts; -increasing the draw angle, the forming forces also increase; -increasing in step depth ∆z, the forces are slight increase, thus no a segnificant infuence.…”
Section: Forces In Isfmentioning
confidence: 99%